Dhikr And Wudu As Therapy On Spiritual Distress In Hypertension Patients - Erlin Indah Kusumadiyanti; Rendi Editya Darmawan; Siti Lestari (Poltekkes Kemenkes Semarang, 2021)
Background: Hypertension is an increase in blood pressure that can pump blood throughout the body within limits above normal. Hypertension is the number one cause of death in the world and is more common in the elderly. This causes various disturbances to a person, one of which is spiritual distress. One of the efforts that can be done to reduce the level of spiritual distress is dhikr and wudu therapy.Purpose: The effect of Dhikr and Wudu as therapy on spiritual distress in hypertantion patients.Methods: this study used a Quasy Eexperiment Nonequivalent Control Group Design study on 36 respondents who had hypertension, which consisted of 18 for the intervension group and 18 for the control group.Results: the results of the Wilcoxon test in the intervention group showed that the p value of changes in the level of spiritual distress before and after being given dhikr and wudu therapy was 0,000, indicating p 0,05. While the results of the Paired Sample T Test in the control group obtained p value of 0.010 indicating p 0,05. The results of the mann whitney test showed that the p value was 0,000 indicating p 0,05Conclusion: there is an effect of dhikr and wudhu therapy on spiritual distress in patients with hypertension.